Spatial analysis of pediatric pulmonary tuberculosis cases aged 0-14 years in West Java Province - Laferani, Yuni; Makful, Martya Rahmaniati; Soviadi, Nabila Vebiana (BKM Public Health and Community Medicine, 2023)
Purpose: Infectious diseases, including tuberculosis (TB), remain a major public health concern worldwide, causing significant morbidity and mortality rates. Despite advances in medical science, the spread of infectious diseases such as TB is not limited by geography or age, and children are particularly vulnerable. As such, this study aims to investigate the global and local spatial effects of pediatric pulmonary TB cases in West Java Province, contributing to understanding TB transmission dynamics and informing effective disease control strategies. Methods: This ecological study employed aggregated data from the 2020 health profile of West Java Province, utilizing all 27 districts and cities. Natural breaks were utilized to classify cases, and data analysis was conducted using GeoDA and QGIS applications. Specifically, GeoDa was employed to conduct Moran's Index and Local Indicators of Spatial Association (LISA) spatial autocorrelation tests, while QGIS was used to generate distribution maps. Results: The study reveals the presence of positive autocorrelation with clustered relationship patterns globally based on the incidence of pediatric pulmonary TB cases (Moran's I: 0.225; P-value: 0.04). The LISA test identifies six districts with significant correlation (Bandung, West Bandung, Cimahi, Ciamis, Majalengka, and Tasikmalaya). Conclusion: The study findings reveal that cases of childhood pulmonary tuberculosis occur in clusters, emphasizing the importance of targeted interventions in areas with high observation values to prevent the spread of the disease to areas with low observation values. Prioritizing program interventions in high-risk areas can help reduce the incidence of children's pulmonary TB cases more effectively.